Solusi Perbedaan Komunikasi Bisnis Antar Generasi di Lingkungan Kerja : Generasi Z, Milenial dan Generasi X - Harmen, Hilma; Ginting, Gevy Ketia; Napitupulu, Dhaet Fretty; Siagian, Yeny Elfina; Saragih, Simon Herbeth Beekham; Ramadhan, Bintang Pajar; Marpaung, Agung Kurniawan Benedictus (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In the era of globalization and digital transformation, organizations encounter persistent challenges in managing business communication across generations. Differences in media preferences, language style, and perceptions of authority often lead to misunderstandings and conflicts among Generation X, Millennials, and Generation Z in the workplace. This study aims to examine the distinctive communication patterns of these three generations and to formulate strategic solutions to enhance cross-generational collaboration. Employing a qualitative approach through library research, the analysis was conducted by reviewing academic literature published between 2013 and 2023 and applying content analysis to identify recurring themes. The findings reveal that Generation X favors formal and structured communication, Millennials adopt a balanced and collaborative style, while Generation Z prioritizes fast, digital, and visual interaction. These variations create communication barriers such as technological gaps, differences in expectations of formality, and divergent interpretations of symbols and language. To address these issues, the study proposes six strategic pillars: integrated multi-channel systems, cross-generational communication training, two-way mentoring, adaptive communication protocols, continuous evaluation, and inclusive leadership. The study contributes to organizational communication research by emphasizing the importance of adaptive strategies to build an inclusive culture and demonstrates practical implications for improving teamwork, productivity, and innovation in multigenerational workplaces.